2016
DOI: 10.1097/rhu.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of American College of Rheumatology–Endorsed Quality Indicators in Rheumatoid Arthritis Patients

Abstract: Excellent adherence to disease-modifying antirheumatic drug therapy and management is likely due to targeting clinical remission. Assessment of disease activity and functional status not only rose each year, but also is higher compared with similar studies. This may be due to an increased awareness of QIs and the utility of objective measures of disease activity. Deficient documentation of prognosis may be due to a lack of awareness of its importance. Suboptimal tuberculosis screening may be an artifact of poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Some studies have described that institution and adherence to T2T guidelines occurred shortly following their appearance, attributing favorable control of disease activity and remission rates to this strategy, which was substantiated by an annual overview prior to and shortly after publication [38]. A retrospective chart review study has previously shown that disease activity and functional assessments increased in number from 2010 to 2012, with excellent treatment and management adherence to quality indicators [41]. In a recent systematic review of real-world T2T evidence [13], it has been shown that over time the rates of achieving remission have gradually improved, though this cannot be attributed to T2T alone.…”
Section: Lag Time In Real-world Institution Of Practice Guidelinesmentioning
confidence: 99%
“…Some studies have described that institution and adherence to T2T guidelines occurred shortly following their appearance, attributing favorable control of disease activity and remission rates to this strategy, which was substantiated by an annual overview prior to and shortly after publication [38]. A retrospective chart review study has previously shown that disease activity and functional assessments increased in number from 2010 to 2012, with excellent treatment and management adherence to quality indicators [41]. In a recent systematic review of real-world T2T evidence [13], it has been shown that over time the rates of achieving remission have gradually improved, though this cannot be attributed to T2T alone.…”
Section: Lag Time In Real-world Institution Of Practice Guidelinesmentioning
confidence: 99%
“…Development of these measures has identified gaps in care, which is associated with negative effects on health-related quality of life [1518]. Recognized gaps in care led to informed quality improvement projects that increased physician adherence to treat to target strategies and use of disease activity measures in rheumatoid arthritis [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Adherence to national and international guidelines certainly increases the quality aspect of effectiveness and improve safety issues (2). Additional quality goals include patient safety, timely and patient-centered care, as well as effective, efficient and socially fair health care (1,(3)(4)(5)(6)(7)(8)(9)(10)(11). An expanded view of quality issues may also contribute to more attractive health care providers' work areas.…”
Section: Introductionmentioning
confidence: 99%